1969
DOI: 10.2105/ajph.59.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and opinions of rural people about mental illness and program services.

Abstract: Delivery of mental health services in rural areas is a serious problem. A project to develop and assess a particular pattern of rural mental health services was started in two North Carolina counties. As part of this project a survey was made of the attitudes and opinions of rural people concerning mental illness, mental health professionals, and related services. The results are reported in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Some studies have indicated high levels of rejection but others have suggested more positive reactions (e.g. Steadman & Cocozza, 1978;Cumming & Cumming, 1957;Ring & Schein, 1970;Edgerton & Bentz, 1969). Most studies on attitudes have been conducted in a variety of Western countries, but several reports come from African (Oyefeso, 1994;Ilechukwu, 1988), Middle-Eastern (El-lslam & Abu-Dagga, 1992) and Chinese (Yang, 1989) cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated high levels of rejection but others have suggested more positive reactions (e.g. Steadman & Cocozza, 1978;Cumming & Cumming, 1957;Ring & Schein, 1970;Edgerton & Bentz, 1969). Most studies on attitudes have been conducted in a variety of Western countries, but several reports come from African (Oyefeso, 1994;Ilechukwu, 1988), Middle-Eastern (El-lslam & Abu-Dagga, 1992) and Chinese (Yang, 1989) cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions that can be drawn from more direct empirical evidence on beliefs and attitudes are limited by incomparability of the studies conducted at different time ~oints. These studies have varied in the populations they have sampled and-particularly for the issue of stigma-in the questions they have asked of study subjects (Belson 1957;Bentz, Edgerton, and Miller 1969;Blizzard 1970;Brockman and D'arcy 1978;Crocetti and Lemkau 1963;Crocetti et al 1974;Cumming and Cumming 1957;Dohrenwend 1966;Dohrenwend and Chin-Shong 1967;Dohrenwend et al 1962;Edgerton and Bentz 1969;Elinson, Padilla, and Perkins 1967;Lemkau and Crocetti 1961 ;Link et al 1999;MacLean 1969;Meyer 1964;Olmsted and Durham 1976;Phillips 1964;Purdue University 1959;Rootman and Lafare 1965;Star 1952Star , 1955.…”
mentioning
confidence: 99%
“…Many studies have shown that the public does not stereotype the mentally ill but is well aware of the diversity of their characteristics (Lemkau & Crocetti 1962;Kentucky Mental Health Planning Commission, 1964;Lemkau, 1962;Edgerton & Bentz, 1969). Therefore question wordings that assume an undifferentiated stereotype on the part of the public may well distort the true nature of the response.…”
Section: Acceptance On the Basis Of The Characteristics Of The Subjectmentioning
confidence: 99%
“…Reported findings of major studies done in the 1960s cast some doubt on the wisdom of such emphasis (Lemkau & Crocetti, 1962;Freeman & Simmons, 1963;Kentucky Mental Health Planning Commission, 1964;Elinson, Padilla, & Perkins, 1967;Edgerton & Bentz, 1969). Even these latter studies, however, exhibit the pervasive influence of the fundamental belief in the public rejection of the mentally ill. Their interpretations are directed toward disproving that the mentally ill are stigmatized, stereotyped, and rejected.…”
mentioning
confidence: 99%